Effectiveness of tyre chips as alternative material in gabion wall to ensure slope stability - Mohammad Amirul Syukri, Md Zin (2018)
Slope failure is a serious geotechnical hazard in many countries in the world including Malaysia. Slope failure is a phenomenon that a slope collapses abruptly due to weakened self-retainability of the earth under the influence of a rainfall or an earthquake. For this project, slope stability will be studied to prevent slope failure from happened. Preventive measure should be taken in order to prevent slope from collapse or fail. For this study, gabion types of retaining wall will be used. A gabion wall is a retaining wall made of stacked stone-filled gabions tied together with wire. Gabion walls are usually angled back towards the slope, or stepped back with the slope, rather than stacked vertically. Stones or gravel is classified as non-renewable resources which will be limited someday in the future. For this study, instead of gravel only, a mixture of tyre chips and stones will be use to fill the gabion wall. An experimental model is developed to simulate the behaviour of the slope under the influence of rainfall with a critical angle of 60º. Based on result analysis, it can be concluded that tyre chips is effective as alternate material for gabion wall to ensure slope stability under small scale.